2017
DOI: 10.1186/s13063-017-2061-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aquatic physical therapy on pain perception, functional capacity and quality of life in older people with knee osteoarthritis: study protocol for a randomized controlled trial

Abstract: BackgroundAquatic therapy promotes short-term benefits for patients with knee osteoarthritis (OA), and it may be the first therapeutic option for this pathological condition. The objective of this study was to investigate the effects of an aquatic therapy program on pain intensity, functional ability, and quality of life in older people with knee OA.Methods/designThis is a parallel, two-arm, open, randomized controlled clinical trial with older people with knee OA. Volunteers will be allocated to an aquatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 23 publications
4
28
1
11
Order By: Relevance
“…buoyancy, which decreases loading of joints, and finally the unique characteristics of water-based exercising which may allow people to perform exercises which otherwise they would be unable to [18,19,25]. Consistent with the results of the present study, they reported that aquatic exercises could improve pain, function, and balance in patients with KOA.…”
Section: Discussionsupporting
confidence: 89%
“…buoyancy, which decreases loading of joints, and finally the unique characteristics of water-based exercising which may allow people to perform exercises which otherwise they would be unable to [18,19,25]. Consistent with the results of the present study, they reported that aquatic exercises could improve pain, function, and balance in patients with KOA.…”
Section: Discussionsupporting
confidence: 89%
“…Segundo Costa et al (2018); Mattos et al (2016) e Alcalde et al (2017), a fisioterapia aquática é considerada uma ferramenta segura e eficaz no tratamento de diversas patologias, acredita-se que essa adaptação ocorra devido às características físicas do meio aquático, a água aquecida e a pressão hidrostática promovam o relaxamento da musculatura, alívio da tensão e a redução de espasmos musculares, que facilita a execução dos movimentos, isso explica a capacidade de realizar os movimentos com melhor precisão e controle, ativando a musculatura, auxiliando no aumento da força muscular perineal. O aumento da resistência impõe uma maior carga nos membros em movimento, o que pode gerar estímulos para aumentar a força muscular desses músculos ativos, a imersão em água pode ser considerada como uma forma de perturbação sensorial e mecânica que é aplicada à pessoa que está em pé na água (Costa et al, 2018), isso pode explicar a melhora da força muscular já que a maioria dos exercícios eram realizados em bipedestação, concomitante com os estímulos para a contração dos músculos do abdomem e assoalho pélvico.…”
Section: Discussionunclassified
“…В конечном итоге, все методы лечения ОА, в том числе ЭП КС, направлены на уменьшение боли и увеличение объема движений в суставе, что, в свою очередь, улучшает качество жизни пациентов. Несмотря на поиск и внедрение новых методов обследования и визуализации, до настоящего времени для этого наиболее часто используются: визуальная аналоговая шкала боли (ВАШ); различные опросники и шкалы [6][7][8][9][10]; измерение окружности бедра, голени и КС; рентгенологическое и ультразвуковое исследование (УЗИ) КС; электромиография четырехглавой мышцы бедра (опосредованно определяющей интенсивность боли); определение амплитуды движений в оперированном суставе [10,11]; 3D-методы визуализации КС.…”
Section: Changes In Gait Parameters During Rehabilitation After Totalunclassified